New record of nuptial gift observed in Trechalea amazonica (Araneae, Lycosoidea, Trechaleidae) - Cruz da Silva, Estevam Luís (2009)
The first record of a nuptial gift in Trechalea amazonica F.O.P.-Cambridge, 1903, is herein presented. The observations were made in the Oriximiná, Pará, northern Brazil. Two males were found on tree trunks near the water, each holding in the chelicerae a small prey wrapped in silk. This is the second confirmed observa- tion of the nuptial gift behavior in the family Trechaleidae, first in the genus Trechalea Thorell, 1869, and later in Paratrechalea Carico, 2005 from southern Brazil. This new observation could be used in phylogenetic and evolutionary studies for this poorly studied spider family.